EVALUASI PROBLEMATIKA MANAGEMEN DAN KURIKULUM TERHADAP MUTUALISASI PENDIDIKAN DI PONDOK PESANTREN SALAFIYAH - Hamdani, Umat Lili; Baharuddin, Baharuddin (Jurnal Kinerja, 2025)
This study aims to evaluate the challenges in management and curriculum within the framework of educational mutualization at Salafiyyah Islamic Boarding Schools (Pesantren), specifically the integration of religious and general education relevant to contemporary societal needs. The central research question explores the extent to which the management and curriculum practices of Salafiyyah pesantren support the development of an integrative and adaptive educational quality that addresses the spiritual, social, and economic needs of students (santri). A descriptive qualitative approach was employed, utilizing techniques such as in-depth interviews, observations, and document analysis. The findings were analyzed by comparing field data with educational management theories, integrated curriculum frameworks, and previous research on similar topics. The findings reveal that Salafiyyah pesantren face several significant challenges, particularly in the areas of human resource management, financial administration, curriculum implementation, and infrastructure development. The existing curriculum remains largely traditional and lacks responsiveness to modern demands. Additionally, the management system is often informal and has yet to adopt a structured and professional approach.. In conclusion, the study underscores the urgency of reforming both management structures and curriculum design to enable pesantren to function as adaptive and contextually relevant educational institutions. Educational mutualization in Salafiyyah pesantren can only be realized through the synergy of curriculum revitalization, professional management practices, and adequate resource support.